Effectiveness of healthy eating interventions among children: A quantitative systematic review. (17th October 2020) - Shorey, Shefaly; Chan, Valerie
Abstract: Aims: This review aimed to evaluate the effectiveness of healthy eating interventions among normal‐weight children. Design: A systematic review of randomized controlled trials. Data sources: Seven databases were searched from the inception of each database until September 2019. Review Methods: A systematic review of quantitative studies was reported according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines and the PRISMA extension for reporting a synthesis without a meta‐analysis. Results: Fifteen studies were included in this review. A meta‐analysis could not be conducted because of the observed heterogeneity across studies. There were mixed effects of the included interventions on healthy eating habits, ranging from effective to not effective. Only a few studies found behavioural determinants effective in enhancing healthy eating. Conclusion: Because of the observed heterogeneity and varied outcome variables, a meta‐analysis could not be conducted, and the overall effectiveness of the included interventions could not be verified. Interventions that were theory based, parent focused, and delivered through the multimodal interactive approach were found to be effective in enhancing healthy eating habits among children. More studies involving peers that are institution based need to be conducted. 摘要: 目的: 本评估旨在评估对正常体重的儿童开展健康饮食干预的有效性。 设计: 随机对照试验的系统评估。 数据来源: 查询了7个数据库自建库初始至2019年9月的文献。 评估方法: 根据系统评估与荟萃分析(PRISMA)指南的首选报告项目和PRISMA扩展内容, 开展了定量研究系统评估, 在未进行荟萃分析的前提下报告评估的综合情况。 结果: 本评估中包含15项研究。由于在研究中已观察到异质性, 未进行荟萃分析。健康饮食习惯中包含的干预手段, 无论是有效或无效手段, 均未出现混合效应。仅有小部分研究发现, 行为决定因素可以有效强化饮食习惯。 结论: 考虑到已观察到异质性和多种结果变量, 可不进行荟萃分析, 涵盖的干预手段的整体有效性可不予验证。研究发现, 基于理论的需要父母关注且通过多渠道交互的方法开展的干预手段可以有效强化儿童的健康饮食习惯。还需要开展更多基于不同机构的同一年龄段儿童的研究。